Ixodes Immune Responses Against Lyme Disease Pathogens - Kitsou, Chrysoula; Pal, Utpal (Frontiers in Cellular and Infection Microbiology, 2018)
Although Ixodes scapularis and other related tick species are considered prolific vectors for a number of important human diseases, many aspects of their biology, microbial interactions, and immunity are largely unknown; in particular, how these ancient vectors recognize invading pathogens like Borrelia burgdorferi and influence their persistence. The analysis of the Ixodes genome and a limited set of transcriptomic data have established that ticks encode many components of classical immune pathways; yet at the same time, they lack many key orthologs of these recognition networks. Therefore, whether a given immune pathway is active in Ixodes ticks and how precisely they exert its microbicidal functions are only incompletely delineated. A few recent studies have suggested that classical pathways like the Janus Kinase/Signal Transducer and Activator of Transcription (JAK/STAT) as well as immunodeficiency (IMD) pathways are fully functional in I. scapularis, and upon challenge with microbes, generate potent microbicidal responses against diverse tick-borne pathogens including B. burgdorferi. These studies also highlight novel concepts of vector immunity that include both a direct and an indirect mode of recognition of pathogens, as well as the influence of the gut microbiome, which ultimately dictates the outcome of a robust microbicidal response. Further understanding of how Ixodes ticks recognize and suppress invading microbes like B. burgdorferi will enrich our fundamental knowledge of vector immunobiology, thereby contributing to the development of future interventions to better control the tick-borne pathogen.